Allocation of Control and User Data Channels for Private UAV Networks - Jyot Singh, Prabhu; de Silva, Rohan (International Journal of Engineering and Technology, 2018)
Unmanned Aerial Vehicle (UAV) industry shows rapid growth in producing sophisticated UAVs for civilian use in recent years. With the invention of private UAV networks, these UAVs can now be used in a UAV network owned by a single organization or a person. For example, a private UAV network gives the ability for a farmer to monitor the farm from one location or to locate people in a natural disaster-stricken area. The wireless communication paths between UAVs and the ground station in a private UAV network play a vital role in transmitting video to the ground station. It is also necessary that the control signals are sent over the private UAV network to the UAVs to control their movements. Since the control signals cannot be delayed and videos received at the ground station should be of high quality, separate channels should be created for user data and control data traffic. In this paper, we present a channel allocation approach for private UAV networks to transfer control data as well as user data. For high quality video transmission, we recommend bonding of basic video channels. This new channelization also avoids congestion and packet drop issues of video and control data traffic in private UAV networks.
Keywords: Channelization; Video and control traffic; Private UAV networks; UAV communication